POSSIBLE CONSEQUENCES OF THE DISPLACEMENT OF MAGNETIC POLES ON THE STRUCTURE AND DYNAMICS OF THE EARTH'S UPPER ATMOSPHERE - Lyakhov A.N.; Zetser Yu.I.; Fuller-Rowell T. (My University, 2006)
The velocity and acceleration of the North Magnetic Pole (NMP) motion has been increasing sharply since the 1970s and has almost doubled (up to 46 km/yr) in the last 30 yr [1]. During the same period, the velocity of the South Magnetic Pole (SMP) displacement decreased, and its motion has practically stopped since 1986. Wandering in the territory of North Canada gave way to stable, almost rectilinear motion of the Russian Arctic sector with linearly increasing acceleration. Given that the present-day trend continues, extrapolation of the NMP coordinates makes it possible to forecast that the NMP will be located in the Severnaya Zemlya Archipelago region by 2050. Such displacement of the NMP can provoke several physical consequences in the earth’s atmosphere and ionosphere.